History of Thought Syuhudi Ismail: A Study of Textual and Contextual Analysis of Prophetic Hadiths - Muhammad Aldi; Moh Toriquddin (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to examine Syuhadi Ismail's thoughts related to the analysis of the Prophet's hadith that prioritizes textual and contextual approaches. The focus of the research is to understand how Syuhadi Ismail combines traditional and modern approaches in understanding hadith, as well as its impact on the development of contemporary hadith studies. This research aims to identify the contribution of his thoughts in dealing with the dynamics of modern society which often requires an understanding of hadith that is relevant to the context of the times. This research uses a qualitative method with a descriptive-analytical approach. Data were collected through a literature study of Syuhadi Ismail's works, including books, articles, and interviews, as well as secondary references from previous research related to this topic. The data were then critically analyzed to identify Syuhadi's thought patterns in applying textual and contextual approaches. The results show that Syuhadi Ismail has an important contribution in balancing between literal understanding of hadith and adjustments to social reality. This thinking opens a space for dialogue between tradition and modernity in hadith studies. Syuhadi's textual approach emphasizes accuracy in understanding the hadith text, while his contextual approach highlights the importance of considering the historical, social, and cultural background when the hadith was delivered. The implication of this research is to provide a foundation for academics and practitioners in developing hadith studies that are adaptive to changing times without ignoring the essence of Islam. Syuhadi Ismail's thought becomes an important model in presenting hadith interpretation that is relevant, moderate, and contributive to the development of Islamic society in the era of globalization. This research contributes to Islamic scientific literature by enriching perspectives in the study of the Prophet's hadith.